2011
DOI: 10.1111/j.1469-8137.2010.03609.x
|View full text |Cite
|
Sign up to set email alerts
|

Where do monomorphic sexual systems fit in the evolution of dioecy? Insights from the largest family of angiosperms

Abstract: Summary• A range of hypothesized evolutionary pathways has been proposed for describing the evolution of dioecy. However, the evolutionary links between other sexual systems not directly involved in dioecy evolution remain largely unexplored, and hence, a comprehensive picture of evolutionary transitions between sexual systems is still lacking.• Here, we explored the diversity and evolution of sexual systems in Asteraceae, the largest family of flowering plants, where almost all sexual systems are present. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 103 publications
(211 reference statements)
0
64
0
1
Order By: Relevance
“…Finally, future work should further explore the distribution and dynamics of reproductive systems in the six families listed in Table 2, as they are interesting candidates for the study of the gynodioecy pathway. Some have already been investigated: Asteraceae (Torices et al, 2011) and the Fragaria genus within the Rosaceae (Spigler et al, 2008(Spigler et al, , 2011. However, to our knowledge, the evolution of dioecy is poorly understood in the majority of genera and families highlighted here.…”
Section: The Routes To Dioecymentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, future work should further explore the distribution and dynamics of reproductive systems in the six families listed in Table 2, as they are interesting candidates for the study of the gynodioecy pathway. Some have already been investigated: Asteraceae (Torices et al, 2011) and the Fragaria genus within the Rosaceae (Spigler et al, 2008(Spigler et al, , 2011. However, to our knowledge, the evolution of dioecy is poorly understood in the majority of genera and families highlighted here.…”
Section: The Routes To Dioecymentioning
confidence: 99%
“…For instance, a statistical association between gynodioecy and dioecy was found in Asteraceae, but this family also includes many monoecious species. In their phylogenetic study of transitions in reproductive systems in Asteraceae, Torices et al (2011) found that the number of transitions to dioecy was lower through the gynodioecy pathway as compared with the monoecy pathway. However, the rate of transition was higher in the former than in the latter (i.e.…”
Section: The Routes To Dioecymentioning
confidence: 99%
See 1 more Smart Citation
“…certain type of reaction to already known situation. If the stress is repeated again, the reaction of the plant is more rapid on the basis of this memory [2,4,6,7,8,9,10,11,30,56,69,80,82,83,87,91]. It is also known that root apices during growth can recognize in advance dangerous soil substrate and avoid them using similar active avoidance root tropism.…”
Section: Importance Of Root Traits For the Seed Growth And Developmentmentioning
confidence: 99%
“…Modern empirical assessment based on comparative data suggests that hermaphroditism gave rise to dioecy mainly through the monoecious pathway (Weiblen et al 2000;Torices et al 2011).…”
Section: Introductionmentioning
confidence: 99%